2010
DOI: 10.15835/nsb213552
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation of Costus speciosus (Koen.) Sm. Using Nodal Segment Culture

Abstract: Nodal segments of Costus speciosus (Koen.) Sm. containing single axillary buds were cultured on Murashige and Skoog medium (MS medium) supplemented with plant growth regulators for inducing plantlets. For breaking of axillary bud dormancy, nodal segments were cultured on 40-70gl -1 sucrose or 1-13 µM adenine sulphate (AdS) supplemented MS basal medium containing 5 µM 6-benzylaminopurine (BAP) and 1µM α-naphthalene acetic acid (NAA). The nodal segments cultured on 1-13 µM AdS, 5 µM BAP, 1 µM NAA and 50gl -1 suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 18 publications
(11 reference statements)
1
5
0
Order By: Relevance
“…It has already been reported that the nodal segments of Costus speciosus show bud-break and shoot multiplication in medium supplemented with BAP, NAA and AdS (Punyarani and Sharma, 2009). In the present investigation, both bud-break and shoot multiplication is possible in media supplemented with BAP and NAA.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…It has already been reported that the nodal segments of Costus speciosus show bud-break and shoot multiplication in medium supplemented with BAP, NAA and AdS (Punyarani and Sharma, 2009). In the present investigation, both bud-break and shoot multiplication is possible in media supplemented with BAP and NAA.…”
Section: Discussionsupporting
confidence: 73%
“…In the present investigation, both bud-break and shoot multiplication is possible in media supplemented with BAP and NAA. The propagules of Costus pictus also produce higher average number of multiple shoot in comparison to propagules of Costus speciosus (Punyarani and Sharma, 2009). However, in both Costus pictus and Costus speciosus, the optimal sucrose concentration for shoot multiplication is 5% sucrose.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Costus speciosus have traditional uses such as food and medicine [4]. Recently the juice of rhizome therapeutically implemented as cooling and relief from head-ache, powder of leaves implemented as antipyretic, the extract acquired by boiling stem part of this plant is used against dysentery and fever, and many cures against diarrhea [5] cough, cuts, burning sensation, scabies, arthritis [6], wounds, constipation, leprosy, for abortion, asthma, inflammations, anemia [7] intestinal pains, nose pain , rash, worm infection, to stop vomiting [8] spermatorrhoea [9] used as antivermin and skin diseases [10]. Earlier studies paid attention on antioxidant, cytotoxicity and antimicrobial effects of plant extracts.…”
Section: Introductionmentioning
confidence: 99%
“…Micro-rhizome formation of Thai black ginger plantlets acclimatized under 6% sucrose were evidently observed (Zuraida et al 2015). Similarly, micro-rhizome in painted spiral ginger (Costus speciosus) was produced using 9% sucrose with 1.7 micro-rhizomes per explant (5.12 g micro-rhizome fresh weight) (Punyarani and Sharma 2010). Thus, the mini-rhizome and microrhizome formation in response to sugar classes and concentration in the culture medium depends on plant species.…”
Section: Discussionmentioning
confidence: 93%